Introduction to Colors for Early Childhood Learning Media at PAUD BAITUL HIKMAH, Bengkulu City - Dhika, Dhika (Gayaku Publisher, 2024)
The purpose of this study is to help children recognize colors faster with learning media using macromedia flash 8 and introduce a new application designed to suit the needs of early childhood. The method used by the author is RAD (Rapid Application Development), a software development methodology that uses minimal planning to support rapid prototyping. This learning media is an option for how PAUD children can play while learning, and are able to communicate with this learning media. Consisting of examples of game objects and questions in the application using macromedia flash 8. In making an interactive media application in recognizing colors at Paud Hikmah. The interactive media application is very easy to use and understand so that PAUD Hikmah children can easily use this application. The menus available are examples of objects, game questions, and profiles. So this study can be concluded that with the application used, it can help learning to recognize colors quickly, because in its use it only by pointing the cursor at this game